First Year Hon. Mention: The Roses Which You Bloom: WRIT 1700A, Writing: Process and Practice. TA: Rosita Georgieva. CD: Jon Sufrin. - Munsayac, Denise (Jan Rehner Prize for Writing, 2022)
In the thoughtful and beautifully written essay, “The Roses Which You Bloom”, the author eloquently takes us on their journey of grieving for their all too recently deceased best friend as they visit her grave. We are readily immersed in their powerful feelings of sadness, remembrance, and reflection. Deftly integrating meaningful insights from Camus and from 2nd Corinthians, in the end, the author movingly rises with her loss to a sense of healing resolution. A powerfully insightful conclusion leaves us all with a deepened understanding of the meaning of friends lost and of the life which lies ahead. This articulate and emotionally driven essay is most worthy of recognition as one of the elite papers of the year.